An extinct Eocene taxon of the daisy family (Asteraceae): Evolutionary, ecological and biogeographical implications - Barreda, Viviana D. (2012)
Background and Aims: Morphological, molecular and biogeographical information bearing on early evolution of the sunflower alliance of families suggests that the clade containing the extant daisy family (Asteraceae) differentiated in South America during the Eocene, although palaeontological studies on this continent failed to reveal conclusive support for this hypothesis. Here we describe in detail Raiguenrayun cura gen. & sp. nov., an exceptionally well preserved capitulescence of Asteraceae recovered from Eocene deposits of northwestern Patagonia, Argentina. Methods: The fossil was collected from the 47·5 million-year-old Huitrera Formation at the Estancia Don Hiplito locality, Ro Negro Province, Argentina. Key Results: The arrangement of the capitula in a cymose capitulescence, the many-flowered capitula with multiseriateimbricate involucral bracts and the pappus-like structures indicate a close morphological relationship with Asteraceae. Raiguenrayun cura and the associated pollen Mutisiapollis telleriae do not match exactly any living member of the family, and clearly represent extinct taxa. They share a mosaic of morphological features today recognized in taxa phylogenetically close to the root of Asteraceae, such as Stifftieae, Wunderlichioideae and Gochnatieae (Mutisioideae sensu lato) and Dicomeae and Oldenburgieae (Carduoideae), today endemic to or mainly distributed in South America and Africa, respectively. Conclusions: This is the first fossil genus of Asteraceae based on an outstandingly preserved capitulescence that might represent the ancestor of MutisioideaeCarduoideae. It might have evolved in southern South America some time during the early Palaeogene and subsequently entered Africa, before the biogeographical isolation of these continents became much more pronounced. The new fossil represents the first reliable point for calibration, favouring an earlier date to the split between Barnadesioideae and the rest of Asteraceae than previously thought, which can be traced back at least 47·5 million years. This is the oldest well dated member of Asteraceae and perhaps the earliest indirect evidence for bird pollination in the family.